Early use of ribavirin in the treatment of Crimean-Congo haemorrhagic fever [Kirim-Kongo kanamali ateşinin tedavisinde erken ribavirin kullanimi] - (:unkn) unknown (DOC Design and Informatics Co. Ltd., 2010)
[No abstract available]